A cost-effective approach to the rapid fabrication of functional metal prototypes - Kuo, Chil-Chyuan (Materiali in tehnologije, 2014)
A quick response to the market is considered as one of the important factors to ensure a company's competitiveness. New products must be swiftly and cost-effectively developed, manufactured and introduced to the market. This work demonstrates a technology for the rapid manufacturing of the metal prototypes for a laptop hinge using both rapid-prototyping and rapid-tooling techniques. A small-batch production for the laptop hinge of about 20 pieces can be obtained economically via a silicone rubber mold using vacuum casting, without applying any plastic injection molding. The fabricated metal prototypes have excellent physical and mechanical properties, which can be used for functional tests. A cost reduction of 75 % and a time saving of 82 % can be achieved. This technology has considerable economic benefits and prospects for broad market applications.
Keywords: laptop hinge; osebni računalniki; metal prototype; ohišja; silicone rubber mold; tečaji; epoxy resin; kovinski prototip; forma; surface roughness; silikonska guma; epoksi smola